2020
DOI: 10.1162/netn_a_00146
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic information in a dynamical model implemented on the human structural connectome reveals spatially distinct associations with age

Abstract: We implement the dynamical Ising model on the large-scale architecture of white matter connections of healthy subjects in the age range 4–85 years, and analyze the dynamics in terms of the synergy, a quantity measuring the extent to which the joint state of pairs of variables is projected onto the dynamics of a target one. We find that the amount of synergy in explaining the dynamics of the hubs of the structural connectivity (in terms of degree strength) peaks before the critical temperature, and can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Our framework is inspired by the Ising Model representation of brain dynamics whereby selforganized patterns of connectivity are formed through the spontaneous fluctuations of random spins (Reichl & Luscombe, 1999). This model has been used to characterize complex microscale dynamics of the human brain (Deco et al, 2008;Kadirvelu et al, 2017;Ostojic & Brunel, 2011;Tkačik et al, 2015), as well as macro-scale interactions (Ezaki et al, 2017;Marinazzo et al, 2014;Nghiem et al, 2018;Niu et al, 2019;Nuzzi et al, 2020;Schneidman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our framework is inspired by the Ising Model representation of brain dynamics whereby selforganized patterns of connectivity are formed through the spontaneous fluctuations of random spins (Reichl & Luscombe, 1999). This model has been used to characterize complex microscale dynamics of the human brain (Deco et al, 2008;Kadirvelu et al, 2017;Ostojic & Brunel, 2011;Tkačik et al, 2015), as well as macro-scale interactions (Ezaki et al, 2017;Marinazzo et al, 2014;Nghiem et al, 2018;Niu et al, 2019;Nuzzi et al, 2020;Schneidman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our framework is inspired by the Ising model representation of brain dynamics whereby self-organized patterns of connectivity are formed through the spontaneous fluctuations of random spins ( Reichl & Luscombe, 1999 ). This model has been used to characterize complex microscale dynamics of the human brain ( Deco et al, 2008 ; Kadirvelu et al, 2017 ; Ostojic & Brunel, 2011 ; Tkačik et al, 2015 ), as well as macroscale interactions ( Ezaki et al, 2017 ; Marinazzo et al, 2014 ; Nghiem et al, 2018 ; Niu et al, 2019 ; Nuzzi et al, 2020 ; Schneidman et al, 2006 ). Unconstrained maximum entropy models (MEM) have been shown to accurately represent spatiotemporal coactivations in neuronal spike trains ( Roudi et al, 2009 ; Schneidman et al, 2006 ; Shlens et al, 2006 ) as well as patterns of BOLD activity ( Ashourvan et al, 2017 ; Cocco et al, 2017 ; Ezaki et al, 2020 ; Watanabe et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such trends suggest alterations in the connectivity of the source EEG network occurring before the onset of focal epileptic seizures. The use of information-theoretic measures as an indicator of phase transitions has been demonstrated using classic spin model in physics [ 50 ], as well as in financial systems [ 51 ] and in the brain: recent studies have shown that the maximal amount of information transfer among units is representative of the critical state on a brain network [ 52 ], and that synergy measures derived from information transfer in a multivariate fashion peak before the transition from disordered to ordered phases [ 53 ]. In this context, the use of measures of information transfer like those presented in this study, possibly integrated with multivariate measures obtained in the context of information dynamics [ 54 ], may have important implications in seizure prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Speaking qualitatively, in a complex system, the synergy measures its capacity to make integration of information whilst redundancy provides robustness to the system; decomposing interactions between variables into synergistic and redundant components illuminates how the system addresses the trade-off between robustness and integration. For example, recent works focusing on the brain at the macroscale have identified high synergy brain regions which support higher cognitive function [13] and are affected by the aging process [14].…”
Section: Introductionmentioning
confidence: 99%